Trauma to the pancreas treated by corporocaudal pancreatectomy - Priario, Julio C; Gilardoni, Federico; de los Santos, Julio (Cirugía del Uruguay, 2020)
A -case of severe pancreatic mJury caused by a knock against a driving wheel, is reported upon. At operation, a tear in the gland at the junction of its head with the body, and steatonecrotic phenomena, were found. In view of the above, pancreattectomy of the body and tail, with splenectomy, was carried out. The post -operative -course, in the light of clinical and laboratory- findings, is dealt with.